Biological roles of RNA m5C modification and its implications in Cancer immunotherapy - Song, Hang; Zhang, Jianye; Liu, Bin; Xu, Jing; Cai, Biao; Yang, Hai; Straube, Julia; Yu, Xiyong; Ma, Teng (Biomarker Research, 2022)
Epigenetics including DNA and RNA modifications have always been the hotspot field of life sciences in the post-genome era. Since the first mapping of N6-methyladenosine (m6A) and the discovery of its widespread presence in mRNA, there are at least 160-170 RNA modifications have been discovered. These methylations occur in different RNA types, and their distribution is species-specific. 5-methylcytosine (m5C) has been found in mRNA, rRNA and tRNA of representative organisms from all kinds of species. As reversible epigenetic modifications, m5C modifications of RNA affect the fate of the modified RNA molecules and play important roles in various biological processes including RNA stability control, protein synthesis, and transcriptional regulation. Furthermore, accumulative evidence also implicates the role of RNA m5C in tumorigenesis. Here, we review the latest progresses in the biological roles of m5C modifications and how it is regulated by corresponding “writers”, “readers” and “erasers” proteins, as well as the potential molecular mechanism in tumorigenesis and cancer immunotherapy.
CRIS-Team Scopus Importer:2022-04-15
Keywords: 5-methylcytosine (m; cancer immunotherapy; Epigenetics; Non-coding RNAs; RNA methylation modification